2018
DOI: 10.1186/s13148-018-0478-z
|View full text |Cite
|
Sign up to set email alerts
|

MEST mediates the impact of prenatal bisphenol A exposure on long-term body weight development

Abstract: BackgroundExposure to endocrine-disrupting chemicals can alter normal physiology and increase susceptibility to non-communicable diseases like obesity. Especially the prenatal and early postnatal period is highly vulnerable to adverse effects by environmental exposure, promoting developmental reprogramming by epigenetic alterations. To obtain a deeper insight into the role of prenatal bisphenol A (BPA) exposure in children’s overweight development, we combine epidemiological data with experimental models and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 47 publications
1
56
0
Order By: Relevance
“…Parabens have been shown to promote adipocyte differentiation in mouse fibroblasts 23 . To evaluate a potential direct effect of parabens on human adipocyte differentiation an established human mesenchymal stem cell differentiation assay was applied 9 . Adipocyte differentiation, assessed by the cell index values of impedance-based real-time monitoring and by the amount of triglyceride storage, was not affected by nBuP exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parabens have been shown to promote adipocyte differentiation in mouse fibroblasts 23 . To evaluate a potential direct effect of parabens on human adipocyte differentiation an established human mesenchymal stem cell differentiation assay was applied 9 . Adipocyte differentiation, assessed by the cell index values of impedance-based real-time monitoring and by the amount of triglyceride storage, was not affected by nBuP exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human adipose-derived mesenchymal stem cells (MSC) derived by a female donor (ATCC, LGC Standards (Wesel, Germany), PCS-500-011; LOT #59753760) and appropriate culture media were purchased from ATCC (LGC Standards,Wesel, Germany, PCS-500-030, PCS-500-040 and PCS-500-050). Cells were cultured under normal conditions at 37°C, 5% CO 2 and 95% humidity according to the manufacturer's instructions 9 . In brief, for adipocyte differentiation MSCs passage 3-5 were seeded at 9.000 cells per cm 2 in a 96-well plate and grown to 70% confluence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, miR-21-a-5p overexpression mitigates BPA obesogenic effect in vivo [147]. In humans, prenatal BPA exposure seems to favor overweight phenotype in children, modifying methylation of CpG sites, including one hypo-methylated CpG in the promoter of the mesoderm-specific transcript gene (MEST) encoding an obesity-related member of the α/β hydrolase fold family [148].…”
Section: Bpa-induced Epigenetic Modifications In Metabolismmentioning
confidence: 99%
“…Exposure to bisphenol-A (BPA) in these mice leads to shifts in DNA methylation levels at the Agouti coat color locus and ultimately, an altered coat color [89]. BPA has also been associated with global and site-specific changes in DNA methylation and histone tail modifications in human observational studies [90][91][92]. A cross-organism study found mouse liver DNA methylation levels at the STAT3 locus were altered in response to perinatal exposure to BPA and were also relevant to adult health outcomes [93].…”
Section: Epigeneticsmentioning
confidence: 99%